Natural infection of triatomines (Hemiptera: Reduviidae) by trypanosomatids in two different environments in the municipality of Ouro Preto do Oeste, State of Rondônia, Brazil - Dionatas Ulisses de Oliveira Meneguetti; Olzeno Trevisan; Luís Marcelo Aranha Camargo; Renato Moreira Rosa (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: This study analyzed the occurrence and the contamination of triatomines by trypanosomatids in Orbignya speciosa (babassu) specimens in the State of Rondônia, Brazil, in two different environments (pasture and woods). METHODS: Capture of triatomines on babassus and microscopic search for trypanosomatids in their digestive tube were carried out. RESULTS: Four hundred ninety-four (494) specimens were captured (Rhodnius prolixus and R.robustus), of which 35.6% of the triatomines were positive for trypanosomatids. CONCLUSIONS: The high index of natural infection along with the abundance of triatomines points out to the necessity to create an epidemiological surveillance system to monitor vector-borne transmission and deepen the studies on the ecology of such vectors in the Amazon.